Perancangan dan Perencanaan Mesin Pemipih Emping Jagung Skala Industri - Gilang Gerry Garnida; Rudy Yuni Widiatmoko; Syahrul Ariq Ismail; Donny Firli Ardiawan; Nuha Desi Anggraeni; Budiana Ruslan (METAL: Jurnal Sistem Mekanik dan Termal, 2020)
UKM XYZ is a corn chips processing business that still uses the traditional method which requires a lot of time and effort. From this problem, the idea emerged to design a corn chip flattening machine which aims to speed up production time and reduce the energy spent processing corn chips. The research stage consisted of the problem identification stage, the goal-setting stage, the drafting stage, and the planning stage. The EOQ Economic Order Quantity method is used to determine the forecast for raw material requirements, the forecasting result is 11.7408 kg. The corn sheller machine is designed to have a capacity of 80 kg/hour, using a 120-watt electric motor, which is connected using a pulley and a belt to 2 axles with a diameter of 30 mm with a length of 620 mm and 570 mm in order to meet the needs of UKM XYZ. On the shaft, a gear is attached to cause rotation of the 2 axles in opposite directions. The piping uses 2 rollers with a diameter of 100 mm and a length of 400 mm. Component materials that have contact with corn use AISI 304 material because this material has high tensile strength and is categorized as a standard material for processing food.